PENGARUH MOTIVASI KERJA TERHADAP KINERJA TENAGA KEPENDIDIKAN DI JURUSAN MANAJEMEN PENDIDIKAN ISLAM - Musdalifah, Musdalifah; Chaerat, Miftahul; Syahri, Nur Alfi (Educational Leadership: Jurnal Manajemen Pendidikan, 2021)
Abstract: The Effect of Work Motivation on the Performance of Education Personnel in the Department of Islamic Education ManagementThis study aims to determine work motivation on the performance of education staff at the Department of Islamic Education Management, Faculty of Tarbiyah and Teacher Training at UIN Alauddin Makassar. This study has two variables, Work Motivation (X) and Education Personnel Performance (Y). The population in this study were all educational staff at the Department of Islamic Religious Education Management, Faculty of Tarbiyah and Teacher Training, and the sample was 3 respondents who were selected based on simple random sampling. Collecting data using a work motivation questionnaire and a performance questionnaire. Data analysis in this study used simple descriptive statistical analysis data, and from the categorization of work motivation the lowest score was 60, the highest score was 72 with an average of 65, and a standard deviation of 6. While the performance obtained the lowest score of 41, the highest score of 44 with an average 43, and a standard deviation of 2. Abstrak: Pengaruh Motivasi Kerja Terhadap Kinerja Tenaga Kependidikan Di Jurusan Manajemen Pendidikan IslamPenelitian ini bertujuan untuk mengetahui motivasi kerja terhadap kinerja tenaga kependidikan pada Jurusan Manajemen Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar. Penelitian ini memiliki dua variabel yaitu Motivasi Kerja (X) dan Kinerja Tenaga Kependidikan (Y). Populasi dalam penelitian ini adalah seluruh tenaga kependidikan pada Jurusan Manajemen Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan, dan sampelnya 3 responden yang dipilih berdasarkan simple random sampling. Pengumpulan data menggunakan kuesioner motivasi kerja dan angket kinerja. Analisis data dalam penelitian ini menggunakan data analisis statistik deskriptif sederhana, dan dari kategorisasi motivasi kerja diperoleh skor terendah 60, skor tertinggi 72 dengan rata-rata 65, dan standar deviasi 6. Sedangkan kinerja diperoleh skor terendah 41, skor tertinggi 44 dengan rata-rata 43, dan standar deviasi 2.